Optimalisasi Strategi Edukasi Wisata Kampung Gambut Siantan Hilir Kalimantan Barat: Pengabdian - Nur Afifah; Giriati; Mustaruddin; Ilzar Daud; Anwar Azazi; Karsim (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to determine the process of processing Anti-Fouling System (AFS) documents by PT. Multi Jaya Samudera at the Main Harbormaster and Port Authority Office (KSOP) Belawan. The research method used is a qualitative descriptive approach through observation, interviews, and document studies related to the AFS document issuance procedure. The results of the study indicate that the AFS document processing is carried out in accordance with the provisions of the International Convention on the Control of Harmful Anti-Fouling Systems on Ships and applicable national laws and regulations. The administrative process includes submitting an application, verifying ship documents, technical inspections, and issuing an AFS certificate. In its implementation, PT. Multi Jaya Samudera faced obstacles in the form of delays in document verification and a lack of understanding of AFS regulations among ship crews, but these can be overcome through intensive coordination with the KSOP and increased socialization of regulations. This study is expected to provide input for shipping companies and port authorities to improve administrative efficiency and compliance with international regulations in efforts to prevent marine pollution.